Kaplan's plot : a novel - Diamond, Jason (Flatiron Books, 2025)
"Elijah Mendes was hoping for a more triumphant return to Chicago. His mother, Eve, is dying of cancer, his business flamed out, and he has nowhere else to go. So he returns to Chicago feeling listless and shattered, worried about how he's going to help his mother despite their chilly relationship. He finds some inspiration when he discovers that their family owns a Jewish cemetery and that a man he's never heard of, his great-uncle Solomon Kaplan, is buried in a plot there. With a new sense of purpose -- and an excuse to talk more deeply with his mother -- Elijah begins pursuing a family mystery of extraordinary proportions. Elijah discovers his grandfather Yitz, Eve's father, was a powerful gangster in the 1920s. She was ashamed and never spoke about him to Elijah. As secrets unravel, the past and present become intertwined, and Yitz's story forces Elijah and Eve to bond in ways they never have before and begin to accept each other, not as who they wish they were but as they both are. Kaplan's Plot is an astonishing balancing act between the ruthless and the tender, the superficial and the truth, by a writer with tremendous promise." --